Long-Term Follow-Up of the Telemonitoring Weight-Reduction Program “Active Body Control” - Gabriele Stumm; Alexandra Blaik; Siegfried Kropf; Sabine Westphal; Tanja Katrin Hantke; Claus Luley (Journal of Diabetes Research)
The Active Body Control (ABC) weight-reduction program is based on telemonitoring of physical activity and nutrition together with telecoaching by weekly counseling letters sent by post or by e-mail. The study presented here reports the results of a 1-year follow-up of 49 patients with the metabolic syndrome who had lost weight with the aid of the ABC program in the preceding year. The weight regain after the second year in patients not receiving any further care (“ABC discontinued” group; n=24) and the potential benefit of continuing with the ABC program with monthly counseling letters (“ABC continued” group; n=25) were investigated. The relative weight changes after the first year had been, respectively, −13.4% and −11.4% in the “ABC discontinued” and “ABC continued” groups, and after the second year they decreased by, respectively, 4.4 and 2.8%. However, this difference in weight regains between the two groups was not statistically significant. It is concluded that three-quarters of the weight loss after 1 year is maintained after the second year. The decision whether to continue with the ABC program after 1 year should be made individually.